OPINI MASYARAKAT DALAM PROGRAM PUSAT PELATIHAN PERTANIAN PEDESAAN SWADAYA MASYARAKAT (P4S) PEMERINTAH KABUPATEN KAMPAR - Rina Hardi; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The poverty rate is happening at the moment is so great that the population growth rate continues to increase each year while employment is a source of livelihood for communities lacking, so that everywhere the unemployment rate is increasing. As in Kampar regency, poverty dominated communities residing in the surrounding countryside, with a source of livelihood as farmers and fishermen rubber workers. Therefore, Kampar District Government established a program that aims to reduce poverty in a program Kampar District Agricultural Training Centre Rural Organization (P4S) and with this program, people can be more advanced Kampar and increased standard of living and Kampar free from poverty. This study aims to determine how the public opinion and to find out how the process of opinion formation in Rural Farming Training Center program Organization (P4S) Kampar District Government.The experiment was conducted in P4S real work in Kubang Jaya subdistrict Siak Hulu, which lasted for two months were from March to April 2014. Research uses descriptive qualitative method of data collection techniques of observation, interviews (interviews) and documentation. Informants in this study amounted to 17 people that the manager of the Institute P4S 5 Real Work in Kubang Jaya District Siak Hulu, nine participants and alumni speakers. Analysis using the model of Interactive Data Analysis with Miles and Huberman collecting data obtained were then processed to be reduced, so that the resulting presented in general conclusion.The results of this study indicate that the opinion appears in Kampar District Government P4S program there are two opinions, namely positive and negative opinions. Second opinions can be seen how a program runs and bring the support of the community and the program continues to run from beginning to the end. Moreover, in the process of opinion formation in the course of which there are P4S communicators, information programs, media, community leaders, and community information.Key word: Opinion, Society, Program, P4S, Government